Artificial osteochondral interface of bioactive fibrous membranes mediating calcified cartilage reconstruction. Issue 37 (31st August 2021) - Liu, Mengtao; Ke, Xiurong; Yao, Yuejun; Wu, Fanghui; Ye, Shuo; Zhang, Lei; Yang, Guojing; Shen, Miaoda; Li, Yifan; Yang, Xianyan; Zhong, Cheng; Gao, Changyou; et al.
Abstract : Calcified cartilage is a mineralized osteochondral interface region between the hyaline cartilage and subchondral bone. Abstract : Calcified cartilage is a mineralized osteochondral interface region between the hyaline cartilage and subchondral bone. There are few reported artificial biomaterials that could offer bioactivities for substantial reconstruction of calcified cartilage. Herein we developed new poly(L-lactide- co -caprolactone) (PLCL)-based trilayered fibrous membranes as a functional interface for calcified cartilage reconstruction and superficial cartilage restoration. The trilayered membranes were prepared by the electrospinning technique, and the fibrous morphology was maintained when the chondroitin sulfate (CS) or bioactive glass (BG) particles were introduced in the upper or bottom layer, respectively. Although 30% BG in the bottom layer led to a significant decrease in tensile resistance, the inorganic ion release was remarkably higher than that in the counterpart with 10% BG. The in vivo studies showed that the fibrous membranes as osteochondral interfaces exhibited different biological performances on superficial cartilage restoration and calcified cartilage reconstruction. All of the implanted host hyaline cartilage enabled a self-healing process and an increase in the BG content in the membranes was desirable for promoting the repair of the calcified cartilage with time. The histological staining confirmed the osteochondral interface in the 30% BG bottom membrane maintained appreciable calcified cartilage repair after 12 weeks. These findings demonstrated that such an integrated artificial osteochondral interface containing appropriate bioactive ions are potentially applicable for osteochondral interface tissue engineering.